2009
DOI: 10.1007/s10499-009-9308-9
|View full text |Cite
|
Sign up to set email alerts
|

Soybean meal and wheat flour, proper dietary protein sources for optimal growth of snail (Semisulcospira coreana)

Abstract: A 10-week feeding experiment was conducted to determine the proper dietary protein source for optimal growth performance of juvenile snails, Semisulcospira coreana. Sixteen isonitrogenous (31% crude protein) and isocaloric (4.2 kcal/g DM) experimental diets (designated as FM, and F-MIX) were formulated to contain 41% fish meal, 42% fermented fish meal, 59% soybean meal, 55% fermented soybean meal, 55% wheat flour with 26% fish meal, 55% fermented wheat flour with 29% fish meal, 50% sesame seed meal with 10% fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Results obtained from the present study clearly indicated that monosex male Nile tilapia O. niloticus fed Maggot meal diet performed better than those fed chicken viscera meal in terms of growth performances. Fish meal is known as the best protein source in aquafeeds and diets containing fish meal generally produce better growth performance in comparison with other protein sources, including animal and plant meals [38]. However, group fed HMM diet performed equally than those fed control diets.…”
Section: Growth Performances and Feed Utilizationmentioning
confidence: 99%
“…Results obtained from the present study clearly indicated that monosex male Nile tilapia O. niloticus fed Maggot meal diet performed better than those fed chicken viscera meal in terms of growth performances. Fish meal is known as the best protein source in aquafeeds and diets containing fish meal generally produce better growth performance in comparison with other protein sources, including animal and plant meals [38]. However, group fed HMM diet performed equally than those fed control diets.…”
Section: Growth Performances and Feed Utilizationmentioning
confidence: 99%
“…The fat content of Rv meat was lower than that of other reported marine snails, freshwater snail (Semisulcospira gottschei 34 ), and land snails (L. aurora, 27 Helix nemoralis, 29 A. fulica, 31 Achatina achatina 33 and Limicolaria spp. 33 ), and within the range of freshwater snail (Semisulcospira coreana 18 ) and land snail (H. a. maxima 30 ). These results indicated that Rv meat was low in fat and rich in protein, and are in good agreement with those reported in marine snails (S. gracilior 25 , H. ternatanus 26 and Cookia sulcata 35 ) and land snail (H. pomatia 28 ).…”
Section: Proximate Analysismentioning
confidence: 99%
“…In Japan, most SCR is incinerated or landfilled directly, and the disposal cost of SCR is 10 000-20 000 yen per ton. Although there were some reports about making SCR into the health food and feed, processing techniques were too complex and cost was too high to use widely (O'Toole, 1999;Pham et al, 2010). The production of ecologic feed by an edible mushroom is a new, simple and economic method to reuse SCR raw materials in SSC.…”
Section: Evaluation Of Ecological Advantagementioning
confidence: 99%